Tinjauan Teologis Tentang Masa Tribulasi Berdasarkan Nubuatan Nabi Daniel Pada Penggenapan Kitab Wahyu - Lasewa, Selvie Kristine; Pangeti, Marhareni (JURNAL ILUMINASI, 2025)
This study aims to describe theologically the prophecy of the Prophet Daniel, namely the occurrence of the great tribulation. In particular, we will examine theologically the prophecy of the Prophet Daniel and when the fulfillment of the prophecy during the tribulation will occur which is written in detail in the book of Revelation, so this study will review it based on Biblical truth. Through research using qualitative descriptive research methods by means of library study, it is hoped that we can provide theological answers based on Biblical truth to the understanding of believers today regarding the truth of the tribulation period. The Tribulation Period is part of God's program to show His omnipotence and His justice in every work of His for humans who do not believe and have no faith in Him, and as a promise to Satan as the author of evil. Through this study, it is hoped that the church will attend and provide correct teaching to church members about what and how the Tribulation Period occurs. So that believers today have the correct understanding so that they do not misinterpret things related to the end times.